Peran Desain dalam Pertunjukan Tumirah (Sang Mucikari) di Prodi Pendidikan Sendratasik Universitas Palangka Raya - Muhamad Romadoni; Jimy O Andin; Andi Arie Astuti; Cahyo Wahyu Darmawan (Universitas Hamzanwadi, 2023)
The role of design, as a visual art that most people think there is a dividing line between the art of motion and sound, will certainly be a new picture in understanding the interrelated relationship in the success of a performance. This is the background related to the research on the role of good design in a performance focused on the